Mechanisms of change - Albert Martin; Ursula Weisenfeld-Schenk; Sigrid Bekmeier-Feuerhahn (Management Revue, 2009)
To understand organizational, strategic and technological change it would be helpful to resort to mechanisms that are responsible for triggering and directing deep-seated social change processes. Propositions about mechanisms have an interesting epistemological status, they take an intermediate stance between law-like and descriptive statements. On the one hand they designate concrete events and on the other they draw on the causality responsible for the emergence of these events. In this article we describe some fundamental characteristics of mechanisms, describe some important change mechanisms and articulate some desiderata for mechanisms-research.
Keywords: 650; change processes; mechanisms; logic of explanation; management of change